2020
DOI: 10.18632/aging.103315
|View full text |Cite
|
Sign up to set email alerts
|

Chronic polypharmacy impairs explorative behavior and reduces synaptic functions in young adult mice

Abstract: A major challenge in the health care system is the lack of knowledge about the possible harmful effects of multiple drug treatments in old age. The present study aims to characterize a mouse model of polypharmacy, in order to investigate whether long-term exposure to multiple drugs could lead to adverse outcomes. To this purpose we selected five drugs from the ten most commonly used by older adults in Sweden (metoprolol, paracetamol, aspirin, simvastatin and citalopram). Five-month-old wild type male mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 80 publications
3
23
1
Order By: Relevance
“…While Fgf1 and Shh were elevated after supplementation with sterols, Igf1 , Egf and Cntf were almost unaffected by sterols but regulated by cuprizone [ 82 ]. The apparent positive effect of plant sterols on the rate of myelination in MS models agrees with the finding of the decreased cholesterol synthesis after monotherapy treatment with statins inhibiting myelinations [ 110 , 111 ].…”
Section: Benefits Of Plant Sterols In Clinical Applicationsupporting
confidence: 85%
“…While Fgf1 and Shh were elevated after supplementation with sterols, Igf1 , Egf and Cntf were almost unaffected by sterols but regulated by cuprizone [ 82 ]. The apparent positive effect of plant sterols on the rate of myelination in MS models agrees with the finding of the decreased cholesterol synthesis after monotherapy treatment with statins inhibiting myelinations [ 110 , 111 ].…”
Section: Benefits Of Plant Sterols In Clinical Applicationsupporting
confidence: 85%
“…15 Polypharmacy for 8 weeks (metoprolol, simvastatin, paracetamol, aspirin and citalopram) in young male mice reduced exploration and spatial working memory. 18 A longitudinal study of treatment from middle to old age, found that polypharmacy regimens with increasing Drug Burden Index 19 (a measure of cumulative exposure to drugs with anticholinergic and sedative effects) impaired physical function in old male mice, which was attenuated by deprescribing. 17 This evidence that polypharmacy with high Drug Burden Index causes impaired function in old age, which is reversible with deprescribing, helps to fill the evidence gap on causation and provides a platform for future studies investigating mechanisms, such as complex drug interactions and the effects on aging biology.…”
Section: Safety and Efficacy Data On Deprescribingmentioning
confidence: 99%
“…Hippocampal mouse tissue and hippocampal rat neurons in primary cultures were lysed in RIPA buffer (50 mM Tris, 150 mM NaCl, 1% Triton X-100, 0.1% SDS) supplemented with protease and phosphatase inhibitor cocktail (Sigma, Aldrich 1:100, 1 mM EDTA and 1 mM EGTA). Western blot was performed as previously described 29 . The following primary antibodies were used: anti-RAR alpha (Abcam ab28767, 1:500), anti-ER alpha (Abcam ab3575, 1:1000), anti-ER-beta (Santa Cruz Biotechnology sc-53494, 1:1000), Arc (Santa Cruz Biotechnology sc-15325, 1:1000), Aromatase (Abcam 18995, 1:1000), phospho-CREB (Cell Signaling 86B10, 1:1000), ADAM 10 (Abcam ab1997, 1:500).…”
Section: Immunoblottingmentioning
confidence: 99%
“…The experiments were performed in white light and by the same experimenters. EPM, DLB and Y-Maze protocols were run as previously described in details 29 . For MWM test, the mice were trained to find a hidden escape (the platform) as previously described 4,16 .…”
Section: Behavioral Testsmentioning
confidence: 99%